Solubilization of Poly{1,4-phenylene-[9,9-bis(4-phenoxy-butylsulfonate)] fluorene-2,7-diyl} in Water by Nonionic Amphiphiles - Burrows, Hugh D. (2009)
In the presence of the nonionic alkyloxyethylene surfactant n-dodecylpentaoxyethylene glycol ether (C12E5), the anionic conjugated polyelectrolyte (CPE) poly{1,4-phenylene-[9,9-bis(4-phenoxy-butylsulfonate)]fluorene-2,7-diyl} (PBS-PFP) dissolves in water, leading to a blue shift in fluorescence and dramatic increases in fluorescence quantum yields above the surfactant critical micelle concentration (cmc). No significant changes were seen with a poly(ethylene oxide) of similar size to the surfactant headgroup, confirming that specific surfactant−polyelectrolyte interactions are important. From UV−visible and fluorescence spectroscopy, dynamic light scattering (DLS), small-angle X-ray scattering (SAXS), cryogenic transmission electron microscopy (cryo-TEM), and electrical conductivity, together with our published NMR and small-angle neutron scattering (SANS) results, we provide a coherent model for this behavior in terms of breakup of PBS-PFP clusters through polymer−surfactant association leading to cylindrical aggregates containing isolated polymer chains. This is supported by molecular dynamics simulations, which indicate stable polymer−surfactant structures and also provide indications of the tendency of C12E5 to break up polymer clusters to form these mixed polymer−surfactant aggregates. Radial electron density profiles of the cylindrical cross section obtained from SAXS results reveal the internal structure of such inhomogeneous species. DLS and cryo-TEM results show that at higher surfactant concentrations the micelles start to grow, possibly partially due to formation of long, threadlike species. Other alkyloxyethylene surfactants, together with poly(propylene glycol) and hydrophobically modified poly(ethylene glycol), also solubilize this polymer in water, and it is suggested that this results from a balance between electrostatic (or ion-dipole), hydrophilic, and hydrophobic interactions. There is a small, but significant, dependence of the emission maximum on the local environment.